Common online early childhood education Patterns during the Corona Pandemic - Elwan, Rania Hamdey; Said, Aml Salah El Deen Muhammed El; Ebrahim, Hanan Abdul Ghaffar Attia; Nounou, Norhan Ali Housni Hassan; Mousa, Noha Awad; , Sabrin; Majed, Alshuridah Sarah; Al-Baker, Wadha Yusef; Faisal, Abdul Rahman bin (CENTRAL ASIA AND THE CAUCASUS, 2021)
This research aims to identify the most common online early education patterns and the reasons why parents choose such patterns. It also aims to identify the most significant statistical differences to be applied to parents according academic qualification, number of children they have, and their occupation, following the descriptive methodology. This has been applied to a sample consisting of 252 parents of the children in early years of education. A questionnaire of three dimensions has been used, and it has been consistent with the subject of the research. This research concluded that the most common online early education patterns are exemplified in getting education through electronic devices such as the educational tablet and mobile phones. This pattern received the first place with a percentage of 75.4%., and an arithmetic mean of 2. 26.. The least common education pattern is exemplified in education through audio platforms (The radio and the Broadcasting), receiving the 13th place with a percentage of 43.65% and an arithmetic mean of 1.31. This is because electronic devices make available the opportunity for direct interaction and communication with the learner. This research concludes that there are no significant differences between the individuals of the sample regarding being applicable owing to the research variables. This research recommends that it is necessary to get parents, and their children trained and qualified to employ and use technology in education.